Pendidikan Karakter di Era Masyarakat 5.0: Strategi dan Tantangan Menuju Pendidikan Individu Berintegritas dalam Lingkungan Digital Terkoneksi (Tarbiyah Suska Conference Series, 2024)
This research discusses the importance of character education in the era of Society 5.0, which is marked by changes in information technology and digitalization, so individuals with integrity, toughness, and strong character are needed to face the complexities and challenges of a connected digital environment. This research identifies relevant strategies for integrating character education into the education system and society. Innovative approaches using information and communication technology can spread character education more broadly and effectively. However, amid the positive impact of technology, it also presents various challenges. The presence of unlimited and varied information can make it difficult for individuals to distinguish between positive and negative values. Therefore, character education must provide clear direction and guidance for individuals. This research uses qualitative methods through library research. Primary data sources were obtained from journals supported by other scientific works. The collected data is analyzed, summarized, and concluded. The research results led to various educational strategies: providing understanding, modeling, simplicity, positive relationships, and adaptive learning. Challenges faced; freedom, personalization, speed of information, interest, innovation, collaboration, technology, critical thinking, confidence, socialization, internet, social interaction, and caring. Solution; digital literacy, character, and inclusive education. It can be concluded that by implementing the right strategy and overcoming existing challenges, it is hoped that character education can play an essential role in forming individuals with integrity and competitiveness in the era of Society 5.0 to create a civilized and harmonious society.